Deficit of Trust and the Decline of Print Media in Lithuania - Valentinavičius, Virgis (Žurnalistikos tyrimai, 2017)
Since the turn of the 21st century, the global decline of print media has become a universally accepted inevitability, along with the broad consensus that this has been brought about by the internet and social media. The ascendancy of new media and the vicissitudes of digital transformation, along with shrinking advertising revenues and the sudden death of classified advertisements, have been piling up pressure on print media worldwide. In the meantime, there are some additional local factors at work in Lithuania that could propel Lithuania to be become one of the first countries in Europe to lose the printed press for good. The decline of Lithuanian print media has been caused not only by technological progress and new innovative media business models, but also by a rather flawed development of the traditional media, as the tested instruments of trust building have faced serious difficulties in taking root in the country’s print media culture. The downturn in the print media points to the limited ability of the Lithuanian press to strike a right balance between the public interest and the efficiency of the business model, as well as to a lack of willingness to create and uphold certain standards of transparency and journalist ethics. Reluctance to discuss deficiencies of the trade in an open way and weak motivation to develop an honest, efficient and credible media regulation environment have also been responsible for the print media’s decline. The vicious circle of the controversial business model which diminishes trust, and low trust which further undermines the financial viability of Lithuanian newspapers are in effect pushing the print media out of the market earlier than pure technological progress is asking for. The predicament of the press is making an impact on the Lithuanian media in general, by narrowing the advertising market. On the other hand, choices made by the public, unfavorable to the printed press, are giving the media valuable directions to move faster towards new forms of media that are more sensitive to the public interest and, accordingly, can command higher trust.